The Afrikaner nation’s search for a Christian identity as a consequence of the Reformed theology that was practiced between 1961 and 1990 - Oliver, Erna (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
The role that the traditional Afrikaner churches played together with their way of practicing theology during the years of struggle, contributed to the fact that a large part of the Afrikaner community, which are mostly Christians, currently find themselves in an identity crisis. The triangular Afrikaner identity framework collapsed when it was declared false, hypocritical and sectarian, not only by the international community but also by those who helped to build this identity from inside. Unable to recover from this onslaught on their identity during the crucial years of transformation, the majority of the Afrikaner community is still struggling to give new meaning and content to their identity framework. Cognitive dissonance can help to identify the issues that need to be redressed. Refocusing on the valuable and sustainable content that should constitute the anchors of the Afrikaner identity frame, this group can implement its Christian calling to bring positive change to South Africa.